Local Government Financing Platforms in China : A Fortune or Misfortune? - Lu, Yinqiu (IMF Working Papers; Working Paper ;, 2013)
China's rapid credit expansion in 2009-10 brought local government financing platforms (LGFPs) into the spotlight. This paper discusses their function, reasons behind their recent expansion, and risks they are posing to the financial sector, local governments, and sovereign balance sheet. This paper argues that LGFPs were a fortune for China in the past, but would turn out to be a misfortune if the causes of the rapid expansion of LGFPs are not addressed promptly. In this context, the paper proposes ways to avoid misfortune by: acknowledging and addressing the revenue and expenditure mismatches at the local government level; establishing a comprehensive framework to regulate and supervise local government budgets; ensuring the sustainability of the financial resources obtained from the sale of land use rights; and developing local government bond markets and promoting financial reforms.